N-Alkyl-2-[4-(trifluoromethyl)benzoyl]hydrazine-1-carboxamides and Their Analogues: Synthesis and Multitarget Biological Activity - Krátký, Martin; Baranyai, Zsuzsa; Štěpánková, Šárka; Svrčková, Katarína; Švarcová, Markéta; Stolaříková, Jiřina; Horváth, Lilla; Bősze, Szilvia; Vinšová, Jarmila (Molecules (Basel, Switzerland), 2020)
Based on the isosterism concept, we have designed and synthesized homologous N-alkyl-2-[4-(trifluoromethyl)benzoyl]hydrazine-1-carboxamides (from C1 to C18) as potential antimicrobial agents and enzyme inhibitors. They were obtained from 4-(trifluoromethyl)benzohydrazide by three synthetic approaches and characterized by spectral methods. The derivatives were screened for their inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) via Ellman's method. All the hydrazinecarboxamides revealed a moderate inhibition of both AChE and BuChE, with IC50 values of 27.04-106.75 µM and 58.01-277.48 µM, respectively. Some compounds exhibited lower IC50 for AChE than the clinically used drug rivastigmine. N-Tridecyl/pentadecyl-2-[4-(trifluoromethyl)benzoyl]hydrazine-1-carboxamides were identified as the most potent and selective inhibitors of AChE. For inhibition of BuChE, alkyl chain lengths from C5 to C7 are optimal substituents. Based on molecular docking study, the compounds may work as non-covalent inhibitors that are placed in a close proximity to the active site triad. The compounds were evaluated against Mycobacterium tuberculosis H37Rv and nontuberculous mycobacteria (M. avium, M. kansasii). Reflecting these results, we prepared additional analogues of the most active carboxamide (n-hexyl derivative 2f). N-Hexyl-5-[4-(trifluoromethyl)phenyl]-1,3,4-oxadiazol-2-amine (4) exhibited the lowest minimum inhibitory concentrations within this study (MIC ≥ 62.5 µM), however, this activity is mild. All the compounds avoided cytostatic properties on two eukaryotic cell lines (HepG2, MonoMac6).
Keywords: GPI-Linked Proteins; Imidazoles; butyrylcholinesterase inhibition; Cholinesterase Inhibitors; GPI-vázané proteiny; imidazoly; buňky Hep G2; acetylcholinesterase inhibition; antimycobacterial activity; Anti-Infective Agents; acetylcholinesterasa; Mycobacterium kansasii; lidé; hydrazides; Mycobacterium avium; Humans; Butyrylcholinesterase; Hep G2 Cells; 4-(trifluoromethyl)benzohydrazide; butyrylcholinesterasa; antiinfekční látky; Acetylcholinesterase; cholinesterasové inhibitory; cytostatic properties; Mycobacterium tuberculosis